Parent decision‐making around the genetic testing of children for germline TP53 mutations. Issue 2 (15th September 2014) - Alderfer, Melissa A.; Zelley, Kristin; Lindell, Robert B.; Novokmet, Ana; Mai, Phuong L.; Garber, Judy E.; Nathan, Deepika; Scollon, Sarah; Chun, Nicolette M.; Patenaude, Andrea F.; Ford, James M.; Plon, Sharon E.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Li‐Fraumeni syndrome is a rare genetic cancer predisposition syndrome caused by germline TP53 mutations. Up to 20% of mutation carriers develop cancer during childhood. The benefits of TP53 mutation testing of children are a matter of debate and knowledge of parent decision‐making around such testing is limited. The current study examined how parents make decisions regarding TP53 testing for their children. METHODS Families offered and those pursuing TP53 testing for their children were identified across the study sites. Qualitative interviews with 46 parents (39 families) were analyzed to describe decision‐making styles and perceived advantages and disadvantages of testing. RESULTS TP53 mutation testing uptake was high (92%). Three decision‐making styles emerged. Automatic decisions (44% of decisions) involved little thought and identified immediate benefit(s) in testing (100% pursued testing). Considered decisions (49%) weighed the risks and benefits but were made easily (77% pursued testing). Deliberated decisions (6%) were difficult and focused on psychosocial concerns (25% pursued testing). Perceived advantages of testing included promoting child health, satisfying a "need to know, " understanding why cancer(s) occurred, suggesting family member risk, and benefiting research. Disadvantages included psychosocial risks and privacy/discrimination/insurance issues. CONCLUSIONS Although empirical evidence regarding the benefits and risks of TP53 testing during childhood are lacking, the majority of parents in the current study decided easily in favor of testing and perceived a range of advantages. The authors conclude that in the context of a clinical diagnosis of Li‐Fraumeni syndrome, parents should continue to be offered TP53 testing for their children, counseled regarding potential risks and benefits, and supported in their decision‐making process. Cancer 2015;121:286–93. © 2014 American Cancer Society.